Furudul Ainiyah Basis Penguatan Pendidikan Karakter di MTsN 2 Kota Malang - Faridi, Faridi; Yogawati, Mariana (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
The Jokowi government pays serious attention to character education. One of the clauses in Strengthening Character Education. Emphasizes the importance of XXI Century skills, including critical thinking skills, creative thinking, communication skills, including mastery of international languages, and collaboration in learning. To achieve these ideal principles of competence, MTsN 2 integrates the values of Furudhul Ainiyah into various activities. This study aims to describe and understand the reasons of MTsN 2 Malang to make Furudhul Ainiyah as a basis for strengthening character education. Describe and understand the implementation of strengthening character education based on Furudhul Ainiyah. This research uses a qualitative approach with a single case study type. Data collection techniques are observation, interviews and documentation. Analysis of the data using the interactive analysis of Miles and Hubermann. The results show that strengthening character education based on Furudhul Ainiyah is in line with the vision and mission of MTsN 2. Strengthening character education based on Furudhul Ainiyah in MTsN 2 is integrated through class, through madrasa culture, and through the community.